Financial landscape transformation : technological disruptions - Grima, Simon; Sood, Kiran; Özen, Ercan (Emerald studies in finance, insurance, and risk management, 2025)
Fintech refers to new technology that improve and automates the financial services delivery system. The main essence of fintech is to help consumers, companies, and business owners to better manage their financial operations, processes, and lives by utilizing algorithms and specialized software that are used on computers and, increasingly, smartphones. Financial Landscape Transformation collects chapters to present the current and probable future state of banking and money with the advent of fintech. It will provide a broader perspective on contemporary financial products, services, technology and regulations, highlighting innovations in financial sector and opportunities created. Contributions from authors of regional diversity provide a range of perspectives and an opportunity to analyse where different countries are up to in terms of Fintech and its applications.